2016
DOI: 10.1002/jmv.24583
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma parvum as a possible enhancer agent of HPV‐induced cervical intraepithelial neoplasia: Preliminary results

Abstract: We read with interest the paper recently published on your journal by Magaña-Contreras et al. [2015] examining the prevalence and the role of sexually transmitted pathogens associated with Human papillomavirus (HPV) infection in cervical samples. However, since the authors were unable to differentiate Ureaplasma parvum (UP) from Ureaplasma urealyticum (UU) in their study, we would like to supplement their observations with the data we collected about HPV-UP co-infection.In a series of 46 asymptomatic patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
3
13
0
1
Order By: Relevance
“…Among them, the Ureaplasma parvum and their related taxa manifested higher richness in the baseline HPV-positive group compared with the baseline HPVnegative group. This is consistent with previous studies in different populations of the world indicating that Ureaplasma parvum was associated with a significantly increased risk of overall HPV infection and increased risk of abnormal cervical cytopathology (20)(21)(22). It was reported that the infection of Ureaplasma could lead to scarring and damage of the epithelium (23), suggesting that infection of the reproductive tract with Ureaplasma parvum might also increase the risk of HPV infection by facilitating viral infections.…”
Section: Discussionsupporting
confidence: 91%
“…Among them, the Ureaplasma parvum and their related taxa manifested higher richness in the baseline HPV-positive group compared with the baseline HPVnegative group. This is consistent with previous studies in different populations of the world indicating that Ureaplasma parvum was associated with a significantly increased risk of overall HPV infection and increased risk of abnormal cervical cytopathology (20)(21)(22). It was reported that the infection of Ureaplasma could lead to scarring and damage of the epithelium (23), suggesting that infection of the reproductive tract with Ureaplasma parvum might also increase the risk of HPV infection by facilitating viral infections.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with the hypothesis that mycoplasmas can exert a synergistic action with hrHPV and possibly act as cofactors in the development of cervical lesions (Ho et al, 1998;Bodily et al, 2011;Tota et al, 2011). Therefore, detecting and eradicating U. parvum infection might contribute to reduce HPV-related carcinogenesis (Drago et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, much attention has been given to the role of vaginal microbiota in the progression of epithelial lesions up to carcinogenesis. Drago et al [63] found a strong correlation between Ureaplasma parvum -HPV co-infection and CIN1. Mitra et al [64] have studied a cohort of 169 women with different degrees of cervical lesions and showed that increasing severity of cervical lesions was associated with higher vaginal microbiome diversity and decreased relative abundance of Lactobacillus species.…”
Section: The Vaginal Microbiota and Hpv Infectionmentioning
confidence: 99%